1992
DOI: 10.1007/bf01570965
|View full text |Cite
|
Sign up to set email alerts
|

The effects of purified 25-kDa lipase from a clinical isolate ofPseudomonas cepacia in the lungs of rats

Abstract: Nanogram quantities of a 25-kDa lipase purified from culture supernatants of Pseudomonas cepacia 90ee, a sputum isolate from a cystic fibrosis (CF) patient, were placed in the lungs of healthy rats. The resulting pathological changes included large amounts of proteinaceous exudate, the accumulation of polymorphonuclear leukocytes and red blood cells, and disorganization of alveolar structure. Pseudomonas cepacia 90ee immobilized in agar beads was also placed in the lungs of rats in a model of chronic infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…SDS/PAGE analysis showed that the purified lipase preparation was homogeneous and the minimum molecular mass of the enzyme was 28 kDa (Figure 5). The molecular mass of lipase from other strains of B. cepacia has been reported to be in the range of 25–36.5 kDa [11,21,22,26,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SDS/PAGE analysis showed that the purified lipase preparation was homogeneous and the minimum molecular mass of the enzyme was 28 kDa (Figure 5). The molecular mass of lipase from other strains of B. cepacia has been reported to be in the range of 25–36.5 kDa [11,21,22,26,29].…”
Section: Resultsmentioning
confidence: 99%
“…The lipase from B. cepacia is considered a virulence factor and is regulated differently from other virulence factors [10]. The pathogenesis of pulmonary infections in cystic fibrosis patients is not completely understood and any molecular characterization of virulence factors would be of obvious importance in understanding the clinical picture [11]. Hence, the purification and characterization of lipase from B. cepacia A.T.C.C.…”
Section: Introductionmentioning
confidence: 99%
“…Production of lipases seems to contribute to the virulence for some species related to pulmonary infections either by hydrolyzing lipid‐rich pulmonary tissue components or by triggering intense inflammatory response (Lonon et al. 1992; Straus et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lipase, protease, extracellular toxic complex, and lipopolysaccharide (LPS) released from the bacteria have been suggested as candidates for the virulence factors which cause pathological changes, such as accumulation of polymorphonuclear leukocytes and proteinaceous exudate in bronchial and alveolar lumina, injury and necrosis of bronchial epithelium, and disorganization of alveolar structure. The specific crucial trigger of the pneumonia and sepsis in B. cepacia infection, however, remains to be clarified (16,20,31,34,39).Among these four candidates, we were interested in LPS, a major component of the outer membrane in gram-negative bacteria, since it is assumed to play a central role in the induction of various pathophysiological responses, such as fever, disseminated intravascular coagulation, and shock in hosts suffering from gram-negative bacterial infections (22,27). LPSs of members of the Enterobacteriaceae, such as Escherichia coli and Salmonella, have been investigated intensively as typical LPSs with high endotoxic activity.…”
mentioning
confidence: 99%
“…Lipase, protease, extracellular toxic complex, and lipopolysaccharide (LPS) released from the bacteria have been suggested as candidates for the virulence factors which cause pathological changes, such as accumulation of polymorphonuclear leukocytes and proteinaceous exudate in bronchial and alveolar lumina, injury and necrosis of bronchial epithelium, and disorganization of alveolar structure. The specific crucial trigger of the pneumonia and sepsis in B. cepacia infection, however, remains to be clarified (16,20,31,34,39).…”
mentioning
confidence: 99%